2015
DOI: 10.1111/dme.12895
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in cross‐sectional associations between impaired glucose regulation, identified by oral glucose tolerance test or HbA1c values, and cardiovascular disease in a cohort of European and South Asian origin

Abstract: AimsWe contrasted impaired glucose regulation (prediabetes) prevalence, defined according to oral glucose tolerance test or HbA1c values, and studied cross‐sectional associations between prediabetes and subclinical/clinical cardiovascular disease (CVD) in a cohort of European and South Asian origin.MethodsFor 682 European and 520 South Asian men and women, aged 58–85 years, glycaemic status was determined by oral glucose tolerance test or HbA1c thresholds. Questionnaires, record review, coronary artery calcifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…It should be considered that HbA1c levels in subjects with impaired glucose tolerance or T2D and its relationship with cardiovascular risk might differ by race and ethnicity, as reported by Eastwood et al This finding may be affected, almost in part, by genetic traits influencing erythrocyte turnover, or alternatively, by nutritional or metabolic factors. Accordingly, some studies showed an increase in the prevalence of subjects with pre‐T2D diagnosed by HbA1c test, whereas others reported a decreased prevalence of subjects with pre‐T2D compared to that obtained according to the OGTT criteria . As suggested by Kanat et al the two tests may highlight different aspects of dysglycaemia and identify different subjects with glucose intolerance.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It should be considered that HbA1c levels in subjects with impaired glucose tolerance or T2D and its relationship with cardiovascular risk might differ by race and ethnicity, as reported by Eastwood et al This finding may be affected, almost in part, by genetic traits influencing erythrocyte turnover, or alternatively, by nutritional or metabolic factors. Accordingly, some studies showed an increase in the prevalence of subjects with pre‐T2D diagnosed by HbA1c test, whereas others reported a decreased prevalence of subjects with pre‐T2D compared to that obtained according to the OGTT criteria . As suggested by Kanat et al the two tests may highlight different aspects of dysglycaemia and identify different subjects with glucose intolerance.…”
Section: Discussionmentioning
confidence: 88%
“…It should be con- TA B L E 3 Cardiovascular risk factors in subjects with overweight/obesity according to the positivity to the different tests profile. 8,11 Conversely, several prospective data suggest that a significant percentage of subjects developing T2D did not present an altered OGTT. 12 It could therefore exist in the group with normal OGTT, a subgroup at higher risk that the HbA1c test could help to identify.…”
Section: Discussionmentioning
confidence: 99%
“…For sensitivity analyses, we estimated the SROC curves separately for Asian and non‐Asian countries because we assume that different genetic factors influence the diagnostic test threshold . The complete results are given Table .…”
Section: Resultsmentioning
confidence: 99%
“…[14] It is unclear at this point whether the greater prevalence of HbA1c defined prediabetes in Asian Indian population translates into cardiovascular risk with some studies from the United Kingdom suggesting that prediabetes defined by HbA1c in South Asian population showed significantly weaker associations with cardiovascular risks compared to western counterparts. [1516]…”
Section: Discussionmentioning
confidence: 99%